2003
DOI: 10.1073/pnas.1533187100
|View full text |Cite
|
Sign up to set email alerts
|

Axonal plasticity and functional recovery after spinal cord injury in mice deficient in both glial fibrillary acidic protein and vimentin genes

Abstract: The lack of axonal regeneration in the injured adult mammalian spinal cord leads to permanent functional disabilities. The inability of neurons to regenerate their axon is appreciably due to an inhospitable environment made of an astrocytic scar. We generated mice knock-out for glial fibrillary acidic protein and vimentin, the major proteins of the astrocyte cytoskeleton, which are upregulated in reactive astrocytes. These animals, after a hemisection of the spinal cord, presented reduced astroglial reactivity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
195
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 285 publications
(211 citation statements)
references
References 38 publications
(44 reference statements)
12
195
1
Order By: Relevance
“…Consequent to this, the reactive astrocytes are able to release inhibitory extracellular matrix molecules known as CSPG, which forms the major component of the glial scar after SCI. Moreover it has been found that mice that are deficient in the GFAP and vimentin genes show significantly improved axonal plasticity and functional recovery after spinal cord injury (69). Our results demonstrated that expression of GFAP at the transcriptional and translational levels was elevated after SCI.…”
Section: Discussionsupporting
confidence: 61%
“…Consequent to this, the reactive astrocytes are able to release inhibitory extracellular matrix molecules known as CSPG, which forms the major component of the glial scar after SCI. Moreover it has been found that mice that are deficient in the GFAP and vimentin genes show significantly improved axonal plasticity and functional recovery after spinal cord injury (69). Our results demonstrated that expression of GFAP at the transcriptional and translational levels was elevated after SCI.…”
Section: Discussionsupporting
confidence: 61%
“…The pharmacological total knock-out of soluble GFAP and vimentin to emulate the combined genetic deficiency of both IFs (Vim GFAP dKO) despite the encouraging results of increased neural regeneration and improvement of CNS functions in Vim GFAP dKO mice (15,52) may come also with some FIGURE 8. WFA differentially regulates cyclin D3 and p27…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, Vim GFAP dKO mice subjected to spinal cord or brain injury recover favorably with improvement of glial scars (14). In fact, the complete absence of type III IFs in Vim GFAP dKO mice helps promote axonal regeneration and regain ambulatory function after spinal cord injury (15). These Vim GFAP dKO mice are also protected from retinal degeneration after experimental retinal detachment (16) and integration of transplanted cells and the extension of neurites in the host retinas of Vim GFAP dKO mice is favored compared with WT mice (17).…”
Section: Gliosis Is a Biological Process That Occurs During Injury Rementioning
confidence: 99%
“…Extensive glial scarring, seen in MMP-2 null mice, should also be considered in this context. Indeed, mice deficient in both GFAP and vimentin, or with selective ablation of reactive astrocytes, show enhanced axonal sprouting and better functional recovery after injury as a result of reduced reactive astrogliosis (Bush et al, 1999;Pekny et al, 1999;Menet et al, 2003).…”
Section: Axonal Plasticity Tissue Sparing and Mmpsmentioning
confidence: 99%